1999
DOI: 10.1002/(sici)1098-2744(199901)24:1<1::aid-mc1>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

ras activity and cyclin D1 expression: An essential mechanism of mouse skin tumor development

Abstract: ras is a family of small GTP-binding proteins that transduce signals from tyrosine-kinase receptors to the nucleus and thus play a role in the regulation of cell proliferation and differentiation. Several lines of evidence have shown that the cell-cycle machinery, specifically the circuit cyclin D1/cyclin-dependent kinase (cdk) 4 and 6-p16-pRb, lies downstream of ras. Point mutations that activate the ras protein and its downstream cascade have been observed in human and experimental tumors. In particular, ras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The ras‐MAPK pathway can regulate the cell cycle through cyclin/cyclin‐dependent kinase complexes. Specifically, activation of the ras‐MAPK pathway produces an increase in cyclin D1 expression [14]. Furthermore, MAPK activation of cyclin D1 expression requires an intact AP‐1 site in its promoter [15, 16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ras‐MAPK pathway can regulate the cell cycle through cyclin/cyclin‐dependent kinase complexes. Specifically, activation of the ras‐MAPK pathway produces an increase in cyclin D1 expression [14]. Furthermore, MAPK activation of cyclin D1 expression requires an intact AP‐1 site in its promoter [15, 16].…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin D1–deficient mice are protected from ras‐mediated (including DMBA/TPA‐induced) tumorigenesis [19], while cyclin D1 transgenics show no enhancement of skin tumor development [20]. These results indicate that cyclin D1 activation is essential but not sufficient for tumor promotion [14]. Because (1) cyclin D1 expression is seen in premalignant lesions and not in normal or hyperproliferating keratinocytes, (2) loss of cyclin D1 expression protects mice from tumorigenesis, and (3) cyclin D1 expression is regulated by AP‐1, it seems probable that the protective action of DN c‐jun involves blocking AP‐1‐regulated expression of cyclin D1 in premalignant cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin D proteins are regulators of G1 to S phase transitions, and they bind to cyclin-dependent kinase 4 (CDK4) and increase its kinase activity, thereby causing the phosphorylation and inactivation of the retino-blastoma tumor suppressor protein (Shaulian and Karin, 2001; Sherr, 1996). Aberrant cyclin D1 expression has been observed in carcinogenesis (Barnes and Gillett, 1998; Fusenig and Boukamp, 1998; Weinstein, 2000), and overexpression of cyclin D1 was reported in several human cancers, including skin cancer (Rodriguez-Puebla et al, 1999). Previous studies have shown that the human cyclin D1 gene regulatory sequences contain two AP-1 binding sites (Albanese et al, 1995; Herber et al, 1994; Shaulian and Karin, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cooperation by cyclin D1 with other genetic alterations is essential for tumor formation in mouse models. Thus, cyclin D1 and c-myc induce lymphomas, and cyclin D1 and ras generate skin tumors in mice (23,24,30,31).…”
Section: Discussionmentioning
confidence: 99%